The Characterization of Serum-Free Media on Human Mesenchymal Stem Cell Fibrochondrogenesis - Ka Yu Carissa Kwan; Ke Li; Yu Yang Wang; Wai Yi Tse; Chung Yan Tong; Xu Zhang; Dan Michelle Wang; Dai Fei Elmer Ker (Bioengineering)
Developing fibrochondrogenic serum-free media is important for regenerating diseased and injured fibrocartilage but no defined protocols exist. Towards this goal, we characterized the effect of four candidate fibrochondrogenic serum-free media containing transforming growth factor beta-3 (TGF-β3), insulin-like growth factor-1 (IGF-1), and fibroblast growth factor-2 (FGF-2) with high/low glucose and with/without dexamethasone on human mesenchymal stem cells (hMSCs) via proliferation and differentiation assays. In Ki67 proliferation assays, serum-free media containing low glucose and dexamethasone exhibited the highest growth. In gene expression assays, serum-free media containing low glucose and commercially available chondrogenic media (COM) induced high fibrochondrogenic transcription factor expression (scleraxis/SCX and SRY-Box Transcription Factor 9/SOX9) and extracellular matrix (ECM) protein levels (aggrecan/ACAN, collagen type I/COL1A1, and collagen type II/COL2A1), respectively. In immunofluorescence staining, serum-free media containing high glucose and COM induced high fibrochondrogenic transcription factor (SCX and SOX9) and ECM protein (COL1A1, COL2A1, and collagen type X/COL10A1) levels, respectively. In cytochemical staining, COM and serum-free media containing dexamethasone showed a high collagen content whereas serum-free media containing high glucose and dexamethasone exhibited high glycosaminoglycan (GAG) levels. Altogether, defined serum-free media containing high glucose exhibited the highest fibrochondrogenic potential. In summary, this work studied conditions conducive for fibrochondrogenesis, which may be further optimized for potential applications in fibrocartilage tissue engineering.